Evaluating the economic viability of hepatitis E virus serological screening among blood donors: A prospective study from India for advancing blood safety - Sangthang Singson; Shamee Shastry; G. Somu; Kiran Chawla (Asian Journal of Transfusion Science)
BACKGROUND: Hepatitis E virus (HEV) stands out as a significant transfusion-transmissible infection, yet it is not included in the screening protocols of many countries. The present study was conducted to assess the cost-benefit implications of incorporating HEV screening among blood donors which is one of the preventive strategies in reducing transfusion transmissible HEV. METHODOLOGY: A decision tree model was prepared to assist the cost-benefit analysis. The serological screening cost of HEV was estimated based with fixed and variable cost. The cost of illness was estimated with direct and indirect cost. Net present value (NPV) and benefit-cost ratio (BCR) was used to measure the economic variability of screening HEV among the blood donors. RESULTS: The unit cost of HEV IgM antibody screening is 1000 INR, and the unit cost of illness due to HEV infection is INR 80,122. The NPV and BCR is INR 6,73,001 and 1.7:1 for the probable transfusion-transmitted HEV infection that was averted by the screening of HEV among the blood donors. CONCLUSION: Considering the risk of probable HEV transmission through blood transfusion, the study suggests that screening HEV among the blood donors is beneficial in averting transfusion-transmitted HEV infection.